Hubungan Frekuensi Kemoterapi dan Kecemasan Terhadap Asupan Energi, Protein, Lemak dan Karbohidrat Pada Pasien Kanker Serviks Di RSUD Dr.Moewardi - Astari, Riza Yulita Kartika, Dr. Mutalazimah, SKM, M.Kes, Elida Soviana, S.Gz., M.Gizi (2015)
Background: Cervical cancer is a tumor that grows in the cervix (cervical). The main cause of cervical cancer is infection of HPV virus (human papilloma virus). One treatment of cervical cancer is chemotherapy. Chemotherapy is a medical treatment that uses chemical drugs which have the purpose of killing cancer cells. The side effects that arise from chemotherapy include nausea, vomiting and gastrointestinal disorders that can affect nutrient intake. Gastrointestinal disorders caused by a person's physiological response to anxiety. Gastrointestinal disorders that occur due to anxiety are loss of appetite, refusing food. Purpose: This study aims to determine the frequency relationship of chemotherapy and anxiety to energy intake , protein, fat and carbohydrates in cervical cancer patients at Dr.Moewardi General Hospital. Method: This research method using observational study design with cross sectional approach. sampling using Consecutive sampling. research samples is 32 samples obtained by observing the inclusion and exclusion criteria. The data retrieval food intake using a 24 hour recall method for 4 days were not consecutive, while for anxiety using questionnaires. Analysis of data using Person Product Moment Correlation test. Result: There is no correlation between the frequency of chemotherapy with nutrient intake (p = 0.165 energy, protein p = 0.096, fat p = 0.8 , carbohydrates p = 0.051). There is no correlation between anxiety with nutrient intake (energy p = 0,462 , protein p = 0.595, p = 0.464 fats, carbohydrates p = 0.098) Research advice: For cervical cancer patients expected to enhance intake of food in order to accelerate the healing process. For the hospital, is expected to improve the nutritional consultation services so that patients who undergo chemotherapy becoming motivated to improve their intake of food